Years delayed gamma-ray and radio afterglows originated from TDE wind–torus interactions. Issue 2 (5th August 2021) - Mou, Guobin; Wang, Wei
ABSTRACT: Tidal disruption events (TDEs) that occur in active galactic nuclei (AGNs) with dusty tori are a special class of sources. TDEs can generate ultrafast and large opening-angle wind, which will almost inevitably collide with the pre-existing AGN dusty tori a few years later after the TDE outburst. The wind–torus interactions drive two kinds of shocks: the bow shocks at the windward side of the torus clouds, and the cloud shocks inside the torus clouds. In a previous work, we proved that the shocked clouds will give rise to considerable X-ray emissions which can reach 10 41 − 42  erg s −1 (so called years delayed X-ray afterglows ). In this work, we focus on the radiations of high energy particles accelerated at both shocks. Benefiting from the strong radiation field at the inner edge of the torus, the inverse Compton scatterings of AGN photons by relativistic electrons at bow shocks dominate the overall gamma-ray radiation. The gamma-ray luminosity can reach $10^{41}~{\rm erg~s^{-1}}(L_{\rm kin}/10^{45}\, {\rm erg \, s^{-1}})$, where L kin is the kinetic luminosity of TDE wind. Synchrotron radiation at bow shocks contributes to the radio afterglow with a luminosity of 10$^{38-39} ~{\rm erg~s^{-1}}(L_{\rm kin}/10^{45}\, {\rm erg \, s^{-1}})$ at 1–10 GHz if the magnetic field is 100 mGauss, and extends to infrared with a luminosity of $\sim 10^{39-40}~{\rm erg \, s^{-1}} (L_{\rm kin}/10^{45}\, {\rm erg \, s^{-1}})$ . Our scenario provides a prediction of the years delayed afterglows in multiple wavebands for TDEs and reveals their connections.